1993
DOI: 10.1080/0108464x.1993.10590074
|View full text |Cite
|
Sign up to set email alerts
|

Settlement Structure and Economic Variation in the Early Bronze Age

Abstract: archaeological evidence has recently improved significantly, both quantitatively as well as qualitatively. Considering the many new sites collectively and retrospectively, it is striking how varied the material is, and how few regularities there are. A well-known example is the highly unexpected environment that surrounded one of the best sites, Bjerre at Hanstholm (Bech 1991). So far only a few sites containing finds of a specific economic nature (i.e. settlements with preserved bones, plant remains, etc.) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It has been suggested that such waste was applied as a type of fertilizer in Denmark starting in the Early Bronze Age (Rasmussen, 1995). Lagerås and Regnell (1999) suggested that farmers introduced simple fertilizing, such as with household waste, as soon as agriculture commenced.…”
Section: Fertilizer Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that such waste was applied as a type of fertilizer in Denmark starting in the Early Bronze Age (Rasmussen, 1995). Lagerås and Regnell (1999) suggested that farmers introduced simple fertilizing, such as with household waste, as soon as agriculture commenced.…”
Section: Fertilizer Categoriesmentioning
confidence: 99%
“…In cultivation layers situated close to farms, fertilizing with household waste has been proposed (Rasmussen, 1995;Boas, 2000). That the presence of Chenopodium album (Henriksen, 2000) on the Glesborg Late Neolithic and Bronze Age fields did not become reduced after centuries of agricultural land use could also be taken as an indication that the farmers followed soil management practices that minimized soil degradation.…”
Section: Aspects Of Land-use Prior To the Catastrophic Aeolian Eventmentioning
confidence: 99%
“…Others have a large flint material, evidence of extensive flint knapping, and an assemblage dominated by specific types of implements. Bronze casting and amber work also seem confined to only a small minority of sites (Earle et al, 1998, p. 15;Rasmussen, 1995).…”
Section: The Early Bronze Agementioning
confidence: 99%
“…The frequent occurrence of plough marks (ard furrows) and occasionally signs of settlements underneath the barrows indicate a form of rotation system, probably with a few years of cereal production followed by a long and irregularly grazed fallow. This land use system is thought to be representative of the predominant agricultural strategy in southern Scandinavia during the Bronze Age (Thrane, 1991;Rasmussen, 1993Rasmussen, , 1995Odgaard, 1994).…”
Section: Introductionmentioning
confidence: 99%